The effect of training and motivation on the performance of Medan City public works (PU) employees - Sihombing, David Rajohim; Sinaga, Deby Fitriani; Tarigan, Inka Agnes Br; Siregar, Melinda (International Journal for Educational and Vocational Studies, 2022)
This study aims to see and determine the effect of training and motivation on employee performance at the Medan City Public Works Department. The research was carried out at the Public Works (PU) department, which is located on Jalan Pinang Baris, Kampung Lalang, Medan Sunggal. research time starts from August 2021 until completion. The population of this study were all permanent employees at the Medan Public Works Department as many as 30 people. And the sample used is the whole of the total population that is 100% with a total of 30 samples. From the results of the statistical test of the training measurement ratio carried out, the standard deviation value was 3.592. On the work motivation variable with a mean value of 43.30, the standard deviation is 3.44. on the employee performance variable with an average value of 34.10 and a standard deviation of 3.36. The results of the F test obtained that the calculated F is 10.59, which is greater than the F table, which is 2.67 with a significance level of 0.05. this means that work motivation and employee performance are significant.